Cancer-Related Stigma and Depression in Cancer Patients in A Middle-Income Country - Medine Yilmaz; Gulcin Dissiz; Ayse Kurtulusoglu Usluoğlu; Sibel Iriz; Filiz Demir; Ahmet Alacacioglu (Asia-Pacific Journal of Oncology Nursing, 2020)
Objective: The aim of the current study are to determine the depression levels of adult oncology patients in the cancer treatment phase and identify both cancer-related stigma and the factors affecting their depression levels. Methods: In this correlational study, 303 adult patients who had been treated at a medical outpatient clinic were surveyed using the convenience sampling method. The “questionnaire for measuring attitudes toward cancer – patient version,” a sociodemographic characteristics questionnaire, and the beck depression inventory were used. A multivariable linear regression model was used for the analysis. Results: The questionnaire and its subscale scores indicated a positive relationship between depression and attitudes toward cancer. The predictive variables for depression were “being younger than 40-year-old” and “feelings of social exclusion,” which accounted for 4% of the total variance. Four factors indicating negative attitudes toward cancer were “being more than 60-year-old,” “higher education,” “low income,” and “feelings of social exclusion,” which accounted for 11% of the total variance. Conclusions: Cancer-related stigma, which underlies patients' emotional and behavioral outlooks, should be reduced in cancer patients. Members of health teams should be sensitive to cancer-related stigma.